Nicotine promotes M2 macrophage polarization through α5-nAChR/SOX2/CSF-1 axis in lung adenocarcinoma - Guiyu Kang; Hui Song; Lei Bo; Qi Liu; Qiang Li; Jingtan Li; Pan Pan; Jingting Wang; Yanfei Jia; Haiji Sun; Xiaoli Ma (Cancer Immunology, Immunotherapy)
Abstract α5-nicotinic acetylcholine receptor (α5-nAChR) plays a vital part in lung adenocarcinoma (LUAD). However, it is not comprehensively understood that how the α5-nAChR affects LUAD. Through diverse bioinformatics analyses and immunohistochemistry, the expressions of α5-nAChR and SOX2 as well as their relations were dissected. α5-nAChR regulated the differentiation of monocytes into M2 macrophages by targeting the STAT3/SOX2/CSF-1 signaling in the coculture system by western blotting and ChIP. α5-nAChR-mediated macrophage-mediated LUAD cell migration via SOX2/CSF-1 signaling in the cocultured medium. Correlations of α5-nAChR, SOX2 and M2 phenotype tumor-associated macrophages (TAMs) were validated in mouse LUAD models and clinical samples. α5-nAChR expression was connected to SOX2 expression, smoking and bad prognosis of LUAD among clinical samples. Nicotine-induced SOX2 expression was mediated by α5-nAChR via STAT3. Additionally, SOX2-mediated macrophage colony-stimulating factor (CSF-1) expression contributed to LUAD progression in vitro. Furthermore, α5-nAChR expression was strongly linked to pSTAT3, SOX2 and M2 macrophage marker CD206 expression and negatively correlated with M1 macrophage marker CD86 expression in vivo. It is indicated that M2 macrophages are mediated by the new α5-nAChR /SOX2/CSF-1 axis in nicotine-related LUAD, which is a potential therapeutic strategy for cancer.